A Cidade das letras no espaço biográfico de Cyro dos Anjos - Tulio Magno de Oliveira Resende (2016)
A writers image is an imaginary construction to be tracked through crosscutting approaches between his/her works and biographical space. Therefore, from a post-structuralistic perspective, directed by the debate aroused by Leonor Arfuch on the possible readings of biographical textual genres, several relations and interpretations that are likely to urge new meanings to a literary text are shown to be possible and allow a multidisciplinary look towards it. As for this essay, such investigations start from the authors figure, which has always been the hub of several debates and controversies throughout literary theorys history. On that account, the present essay intends to propose a study of the construction of writer Cyro dos Anjos image, which extends to that of an intellectual, and through that enlargement of meaning, come to analyze some aspects that characterize and allow the observation of facts related to the literary ambience of a certain time and place here regarded as the city of letters, a concept developed by Ángel Rama , paying close attention to writer Cyro dos Anjos performance in this panorama.